Eye-Tracking Metrics for Figure-Copying Processes in Early- vs. Late-Onset Alzheimer's Disease - Kim, Ko Woon; Choi, Jongdoo; Chin, Juhee; Lee, Byung Hwa; Na, Duk L. (Frontiers in Neurology, 2022)
Visuospatial dysfunction is a common symptom in patients with Alzheimer’s disease (AD). To more focus on copying processes rather than on finally completed figures, we conceptually split the copying processes into three stages: visuoperceptual function, visuoconstructional function, and working memory function. We constructed perceptual and working spaces to investigate the different stages of copying, and then we compared the number and duration of fixations and saccades and the number of switches across the two spaces. We used eye-tracking glasses to assess eye-tracking metrics in early-onset AD (EOAD) patients, late-onset AD (LOAD) patients, and normal control (NC) participants while they copied the simplified Rey-Osterrieth Complex Figure Test. Regarding eye metrics on the perceptual space, the number and duration of fixations were greater in both groups of AD patients than in the NC participants group (number: EOAD vs. NC: P < .001, LOAD vs. NC: P = .003/ duration: EOAD vs. NC: P < .001, LOAD vs. NC: P < .001). On the working space, the number and duration of fixations were greater in the EOAD patients than in the LOAD patients and NC participants (number: EOAD vs. LOAD: P = .007, EOAD vs. NC: P = .001/ duration: EOAD vs. LOAD: P = .008, EOAD vs. NC: P = .002). The number of saccades was higher in EOAD patients than in NC participants (P < .001). The eye-tracking metrics from the simplified RCFT correlated with the neuropsychological test scores. EOAD and LOAD patients achieved the same level of performance at the simplified and original RCFT scores. However, EOAD than LOAD patients showed longer fixation duration on the working space and more frequent switching between the perceptual and working spaces, which may reflect more cognitive efforts to achieve the same level of performance.